2016
DOI: 10.1080/13607863.2016.1268095
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and alcohol use among older adults: a comparison with middle-aged adults

Abstract: Objectives This study compared the association between social networks and alcohol consumption among middle-aged (MA) and older adults (OA) to better understand the nature of the relationship between those two factors among OA and MA. Method We examined Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions. Current drinkers aged over 50 were subdivided into two age groups: MA (50–64, n = 5214) and OA (65 and older, n = 3070). Each age group was stratified into drinking levels (low-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…Shrinking social networks and deaths from COVID-19 leaves many without coping resources (65). Social isolation, loneliness, death of loved ones, complicated grief, and prolonged bereavement are associated with problematic substance use and relapse both in younger and older adults, and can adversely affect mental health (17,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Bereavement and Loneliness: Lasting Effects Of The Covid-19 mentioning
confidence: 99%
“…Shrinking social networks and deaths from COVID-19 leaves many without coping resources (65). Social isolation, loneliness, death of loved ones, complicated grief, and prolonged bereavement are associated with problematic substance use and relapse both in younger and older adults, and can adversely affect mental health (17,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Bereavement and Loneliness: Lasting Effects Of The Covid-19 mentioning
confidence: 99%
“…Older and younger adults may vary in their stressors and other biopsychosocial factors associated with alcohol use disorders. Retirement, reduced social networks, loss of loved ones and social isolation may contribute to the onset and maintenance of alcohol and drug use in older adults ( 1 43 24 23 Akerlind and Hornquist, 1992; Perreira and Sloan, 2001; Kuerbis and Sacco, 2012; Kim et al, 2018; Kuerbis et al, 2018 ). Older adults may also have longer exposure to substances (early onset) and face more severe health outcomes ( Moos et al, 2009 ) leading to early retirement and early needs for elderly care services.…”
Section: Previous Alcohol Typology Studiesmentioning
confidence: 99%
“…Plant volatiles serve as essential cues to insects searching for resources, mates, and oviposition sites (Juma et al, 2016;Hanks et al, 2018;Houjun et al, 2018;Xu and Turlings, 2018). The reception of host-plant volatiles in Lepidoptera is accomplished through a highly sensitive chemosensory system on the antenna, FIGURE 3 | Dosage responses of H. cunea adults EAG to selected host volatile components.…”
Section: Discussionmentioning
confidence: 99%
“…For example, plant volatiles are likely to serve as attractants to insects over a larger spatial range and pheromones are more likely to help guide the insects over a relatively short distance to mate in parasitoids (Xu and Turlings, 2018). Host-derived volatiles play an important role as oviposition stimulant for Lepidopterans, such as tobacco hornworm Manduca sexta, Ostrinia latipennis, C. pomonella, and the stem borer Busseola fusca (Mechaber et al, 2002;Li and Ishikawa, 2006;Lombarkia and Derridj, 2008;Juma et al, 2016). However, our results showed that female oviposition rates and fecundity of H. cunea did not show sensitivity toward the volatiles from host plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation